A CRITICAL ANALYSIS OF SUSTAINABLE SUPPLY CHAIN MANAGEMENT IN HIGHER EDUCATION DURING AND POST COVID-19 - Alabduljabbar, Dr. Shatha Ayub; Bhanot, Dr. Astha (The journal of contemporary issues in business and government, 2021)
This research paper analyzes Sustainable Supply Chain Management during and Post Covid-19.A novel Covid-19 has developed a great danger to the health of the people in the entire World and also severely affected 210 countries and its areas. A profound problem disturbed social activities, global trade, industries and educational institutions by confinements and social distance. An outbreak of Covid-19 has intensified human sorrows by economic loss. The impacts are considerable on society, economy, health, environment and education. Especially education was affected more compared to others. Each and every country was trying to protect the disease transmission. And government introduced many remedies like isolating, testing, treating patients, banning public groupings and lockdown for some months. This paper focuses on higher education sustainability during and Post Covid-19. It also presents the important objective to examine the effect of Covid-19 pandemic on the educational sector. The paper highlights the experience of Yanbu University Colleges in Saudi Arabia. It purposes to give exploration idea for examining sustainability supply chain management in a higher education especially during and Post Covid-19 situation.